Detection of Trends of Internet Traffic using Sequential Patterns - Jeļinskis, J.; Lauks, G. (Elektronika ir elektrotechnika, 2009)
We propose a new method of possible trend detection in the internet traffic by using sequential pattern analysis. The main steps of this method, such as the template pattern discovery in time-series data and pattern comparison and matching for sequential pattern analysis, are analyzed and the possible constraints and problems are pointed. Experimental data are depicted and future research subjects are described. Ill. 6, bibl. 9 (in English; summaries in English, Russian and Lithuanian).